Structural Study of a Flexible Active Site Loop in Human Indoleamine 2,3-Dioxygenase and Its Functional Implications - Álvarez, Lucía (Biochemistry, 2016)
Human indoleamine 2,3-dioxygenase catalyzes the oxidative cleavage of tryptophan to N-formyl kynurenine, the initial and rate-limiting step in the kynurenine pathway. Additionally, this enzyme has been identified as a possible target for cancer therapy. A 20-amino acid protein segment (the JK loop), which connects the J and K helices, was not resolved in the reported hIDO crystal structure. Previous studies have shown that this loop undergoes structural rearrangement upon substrate binding. In this work, we apply a combination of replica exchange molecular dynamics simulations and site-directed mutagenesis experiments to characterize the structure and dynamics of this protein region. Our simulations show that the JK loop can be divided into two regions: the first region (JK loop(C)) displays specific and well-defined conformations and is within hydrogen bonding distance of the substrate, while the second region (JK loop(N)) is highly disordered and exposed to the solvent. The peculiar flexible nature of JK loop(N) suggests that it may function as a target for post-translational modifications and/or a mediator for protein–protein interactions. In contrast, hydrogen bonding interactions are observed between the substrate and Thr379 in the highly conserved “GTGG” motif of JK loop(C), thereby anchoring JK loop(C) in a closed conformation, which secures the appropriate substrate binding mode for catalysis. Site-directed mutagenesis experiments confirm the key role of this residue, highlighting the importance of the JK loop(C) conformation in regulating the enzymatic activity. Furthermore, the existence of the partially and totally open conformations in the substrate-free form suggests a role of JK loop(C) in controlling substrate and product dynamics.